The Effect of Gym Ball on Reducing Low Back Pain, Labor Pain, and Progress in Primigravida Labor - Rosidah Solihah; Metty Nurherliyany; Sandriani Sandriani; Nayundha Indicasari Putri (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: The average third-trimester pregnant woman often experiences lower back pain and it is caused by a shift in the woman's center of gravity and her posture becoming increasingly lordotic due to the growing weight of the uterus, excessive bending, walking without rest, and lifting weights. Pregnancy exercise with a ball or gym ball is an effective way to reduce back pain during the third trimester of pregnancy. In addition to reducing pain during pregnancy and childbirth, the gym ball can also accelerate labor in primigravida and increase the effectiveness of sleep in third-trimester pregnant women. Objective: This literature review was conducted to find references related to the Gym Ball in reducing low back pain, labor pain, and labor progress. Method: This literature review was conducted using the PRISMA method (Preferred Reporting Items for Systematic and Meta-Analyses). Result: Based on the articles that have been analyzed, it can be determined that using the gym ball can reduce lower back pain in the third trimester, ease labor pain, and accelerate the progress of labor in primigravida mothers. Conclusion: The gym ball can provide relaxation to the muscles so that it can reduce pain in the back, reduce labor pain, accelerate labor, and improve the mother's sleep quality. Referring to that, it is suggested that all health facilities be able to provide gym ball services, which are given to pregnant women since the third trimester as one of the preparatory activities for childbirth.